Remission of refractory esophageal lichen planus induced by tofacitinib - Bieneck, Valentina; Decker, Annegrit; Schmitt-Graeff, Annette; Kreisel, Wolfgang; Schauer, Franziska (Zeitschrift für Gastroenterologie, 2024)
As of now, there exists no established therapy for ELP. Retinoids, which are standard in treating cutaneous LP, do not exhibit positive effects in ELP. While topical glucocorticosteroids often yield favorable responses in esophageal inflammation, some cases prove recalcitrant or refractory. In such instances, various immunosuppressive therapies have been attempted with variable success.This report details a severe case of ELP that showed resistance to prednisolone, acitretin, alitretinoin, adalimumab, tacrolimus, hydroxychloroquine plus mycophenolate mofetil, and cyclophosphamide. The initiation of the JAK inhibitor tofacitinib induced an impressive clinical, endoscopic, and histological remission. This positive response to a JAK inhibitor is discussed in the context of our evolving understanding of the immune-mediated pathogenesis of this disease.
Keywords: lichen planus; JAK-inhibitor; esophagus; autoimmunity; dermatology; mucosal detachment; endoscopy